Vocal fold paralysis: 10 years experience - Sousa Ribeiro, Inês (2018)
Introduction: vocal cord paralysis is a fundamental entity and challenging in its diagnosis and therapy. This study aims to evaluate the 10 years experience of the ENT Department of CHVNG/E.Material and methods: patients with the diagnosis “Vocal Cord Paralysis” that were submitted to surgery and that were evaluated by nasofibrolaryngoscopy were screened from 1 July 2004 to 30 June 2014. We evaluated the etiology, diagnosis and management, and outcome.Results: The most frequent etiology is iatrogenic (66.4%), mostly thyroid surgery (90.7%). Dysphonia is the most common symptom (82.3%), and dysphagia and dyspnea may occur. The diagnostic starts with a careful medical history and directed tests. 74.3% of patients were initially oriented to speech therapy, with good results in cases of unilateral paralysis (8.5% full recovery, 49.1% improved glottal function). In refractory cases, patients underwent surgical intervention: in unilateral paralysis, laryngeal injection medialization (34,8%); in bilateral paralysis, temporary or permanent lateralization procedure according to the evolution over time (65.9%), and tracheostomy (19.1%). 13.3% of patients required at least one reoperation for symptomatic control.Conclusion: The vocal cord paralysis is not a disease in itself but a manifestation of a basic condition, so the variable etiology requires an accurate diagnostic study. The therapeutic approach addresses the symptomatic relief, either through conservative or surgical techniques, allowing to restore partially or totally the speech, respiratory and digestive function.